Assessment of potential drug-drug interactions among outpatients receiving cardiovascular medications at Jimma University specialized hospital, South West Ethiopia - Chelkeba, Legese; Alemseged, Fessahaye; Bedada, Worku (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The quality of pharmacotherapy is highly dependent on the process of choosing a drug in relation to nature of the disease. Several factors should be considered in choosing optimal pharmacotherapeutics strategy including efficacy, safety, availability and cost of the drugs. The objective of this study was to assess potential drug-drug interactions and risk factors in outpatients taking cardiovascular drugs at Jimma University specialized hospital. Methods: A cross-sectional study was conducted from Feb. to April, 2011on patients visiting the cardiac clinic of Jimma University Specialized hospital. A sample of 332 outpatients who were taking cardiovascular medications at study clinic was studied. MicroMedex software was used to screen drug-drug interactions and SPSS for windows software versions-16.0 was used for data analysis. Results: A total of 1249 drugs with average of 3.76 drugs per prescription were prescribed for the 332 patients. The frequency of potential DDIs was found to be 241 (72.6%). Among these 200 (67.3%) were of "moderate" severity and 164 (55.2%) were delayed in onset. The most common potential DDI observed was between Enalapril and Furosemide (20%). Patients who prescribed many drugs (AOR=4.09; P=0.00) by medical intern had a higher risk of developing potential DDIs (AOR=4.6; P=0.00). Conclusions: Patients with cardiovascular disorders are subjected to high risk of potential drug-drug interactions and the number of drugs prescribed and educational level of the prescribers has a high significantly associated with the occurrence of potential drug-drug interactions. Therefore, it is imperative that further studies need to be conducted to identify reasons for and tackle the problem and provide appropriate mechanisms for management.